Physiological and Biochemical Changes during Seed Maturation of Bottle gourd - PIYUSH SHARMA; RAJINDER SINGH; SEEMA BEDI (Seed Research, 2026)
The poor seed quality of bottle gourd seed is due to due to non-synchronous fruit setting in bottle gourd and all the fruits do not reach maturity at the time of plant senescence resulting in mixture of mature and immature seeds. This results in poor seed yield and reduction in seed quality. The present investigation was conducted for two years during 2014 and 2015 at Punjab Agricultural University, Ludhiana to determine the physiological maturity of bottle gourd (Lagenaria siceraria) seeds in relation to fruit age and pre-storage duration. The fruits were harvested at 25, 35 and 45 days after pollination (DAP) and stored for 0, 10, 20 and 30 days before extraction of seed. Each female flower was tagged date wise after doing pollination with hand to monitor fruit age. Numbers of developed seeds, 100 seed weight, germination, speed of germination, seedling length and vigour indices, total lipids of seeds increased with delay in harvesting and increase in the pre-storage duration in both the years. Maximum seed weight, germination, vigour indices, lipid content were observed when fruits were harvested 45 DAP and pre-stored for at least 10 days in both the years. However, sugar content of the seeds decreased with delay in fruit harvesting and pre-storage duration.